Perceived Pain or Gain: Role Identity, Gratification, and the Well-Being of Hybrid Entrepreneurs - Albrecht, Nadine; Reinecke, Pauline Charlotte; Baum, Matthias; Isidor, Rodrigo; Boddington, Monique Ingrid (Entrepreneurship Theory and Practice, 2026)
Hybrid entrepreneurship—pursuing a venture while maintaining paid employment—can enhance or undermine well-being. Based on a longitudinal, qualitative study, we identify two distinct trajectories shaped by envisioned future selves: delayed entrepreneurial gratification with cumulative strains on well-being, and present gratification with supportive effects on well-being. Drawing on role identity theory, we theorize how role internalization and identity centrality relate to the well-being experiences of hybrid entrepreneurs and introduce gratification and rationalization as ways to handle strains on well-being. Our findings offer a deeper understanding of the divergent well-being experiences in hybrid entrepreneurship.